“On Social Media Science Seems to Be More Human”: Exploring Researchers as Digital Science Communicators - Koivumäki, Kaisu (2020)
In contemporary media discourses, researchers may be perceived to communicate something they do not intend to, such as coldness or irrelevance. However, researchers are facing new responsibilities concerning how popular formats used to present science will impact science’s cultural authority (Bucchi, 2017). Currently, there is limited research on the microlevel practices of digital science communication involving researchers as actors. Therefore, this qualitative study explores how digital academic discourse practices develop, using the tweeting and blogging of researchers involved in a multidisciplinary renewable energy research project as a case. The results of a thematic analysis of interviews with researchers (n = 17) suggests that the researchers’ perceptions form a scale ranging from traditional to progressively adjusted practices, which are labelled ‘informing,’ ‘anchoring,’ ‘luring,’ and ‘maneuvering.’ These imply an attempt to diminish the gap between science and the public. The interviewees acknowledge that scientific facts may not be interesting and that they need captivating means that are common in the use of new media, such as buzzwords and clickbait. It appears that trials and experimentation with hybrid genres helped the researchers to distinguish the contours of digital academic discourses. The implications support suggestions to broaden the trajectories of expertise and communication, including issues of culture and identity, trust, and the relevance of science. It is argued that scientists’ embrace of new media channels will refine some articulations of the mediatization processes, and these findings support recent suggestions that mediatization could also be conceptualized as a strategic resource.